Physiology and Pharmacology of Two-Pore Domain Potassium Channels - Kim, Donghee (Current Pharmaceutical Design, 2005)
Searching the DNA database has led to the identification of a class of K+ channels now referred to as two-pore or tandem-pore domain K+ (K2P) channels. The K2P channel is structurally unique in that each subunit possesses two poreforming domains and four transmembrane segments. In mammals, sixteen K2P channel genes have been identified, and their mRNA transcripts are expressed in many different cell types and tissues. K2P channels have properties of background or leak K+ channels, and therefore play a crucial role in setting the resting membrane potential and regulating cell excitability. Some K2P channels are activated by certain physical and chemical factors such as lipids, volatile anesthetics, heat, oxygen, protons and membrane tension. Some K2P channels are targets of agonists that bind receptors coupled to different types of G proteins, and are probably involved in a variety of neurotransmitter and peptide hormone-mediated signal transduction processes. Such diverse properties of K2P channels suggest that they are involved in many different physiological and pathophysiological processes. Therefore, K2P channels could become potentially important therapeutic targets for the treatment of various pathological conditions.
Keywords: free fatty acids